PENENTUAN NILAI KONDUKTIVITAS HIDROLIK TANAH TIDAK JENUH MENGGUNAKAN UJI RESISTIVITAS DI LABORATORIUM - Asmaranto, Runi; Aryani Soemitro, Ria Asih; Anwar, Nadjadji (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Electrical resistivity can be used to identify geotechnical parameters such as water content, liquid limit, plastic limit and unit weight. It is known that the hydraulic conductivity values can be predicted based on soil properties, so that should be determined through resistivity laboratory test. Some researchers explained that unsaturated soil hydraulic conductivity correlated with soil-water characteristic curve (SWCC), thus the estimated values of hydraulic conductivity using a resistivity test is very important to be developed by observing the behavior of the soil.This study examines changes in hydraulic conductivity of unsaturated soil based on laboratory resistivity test. The results are compared with Gardner (1958) and Campbel (1973) empirical methods. The results show that the unsaturated soil hydraulic conductivity correlates well with the empirical methods used.Keywords: soil-water characteristic curve, hydraulic conductivity, unsaturated soil, suction